Who networks? – A meta-analysis of networking and personality. Issue 5 (2nd July 2020) - Bendella, Hadjira; Wolff, Hans-Georg
Abstract : Purpose: Networking refers to goal-directed behaviors focused on building and cultivating informal relationships to obtain career-related resources. According to Gibson et al. 's (2014) model, personality traits represent prominent and important antecedents of networking. This study seeks to provide robust evidence on relationships between personality and networking by summarizing prior research using meta-analytical tools. Design/methodology/approach: The authors classify linking attributes between networking and personality into social, idea-related, task-related and affective behavioral domains and additionally include three compound traits that relate to several domains. They investigate two potential moderators: internal vs. external networking and prominent networking measures. Their comprehensive literature search identified 41 studies with 46 independent samples. Findings: The authors find that social, idea-related and task-related traits have positive relationships with networking of medium effect size, whereas affective traits exhibit small but significantly positive effects. The compound trait of proactive personality appears to be the best predictor of networking. Moderator analyses indicate that there were hardly any differences concerning internal and external networking and also prominent measures. Originality/value: The present study goes beyond narrative reviews contributing the first quantitative summary of these relationships. It identifies four behavioral domains that represent characteristics relevant to networking. The findings largely corroborate, but at times correct, narrative reviews on dispositional antecedents of networking. The authors highlight the importance of compound traits that have yet been overlooked by narrative reviews (e.g. self-monitoring).